ACM SIGGRAPH 2007 Educators Program 2007
DOI: 10.1145/1282040.1282061
|View full text |Cite
|
Sign up to set email alerts
|

Team-based pedagogy for CS102 using game design

Abstract: Computer science teachers often struggle with design programming assignments that both introduce students to object-oriented design and provide meaningful opportunities for students to develop object-oriented programming skills. As a result, teachers seek creative alternatives for educating the next generation of computer scientists. Using the context of game design, we identify a team-based pedagogical strategy to assist students with understanding object-oriented design principles. Team-based pedagogy includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In CS, in particular, it has been found that this student-centred instructional approach has many advantages, including a high level of engagement, better academic performance for weaker students, enhanced programming skills and confidence in the ability to program (Elnagar & Ali, 2013;Kirkpatrick & Prins, 2015;Lasserre & Szostak, 2011;Rankin et al, 2007). This study will examine whether some of these advantages are observed in a new postgraduate course we created: Programming and Systems Development (ProgSD).…”
Section: Team-based Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In CS, in particular, it has been found that this student-centred instructional approach has many advantages, including a high level of engagement, better academic performance for weaker students, enhanced programming skills and confidence in the ability to program (Elnagar & Ali, 2013;Kirkpatrick & Prins, 2015;Lasserre & Szostak, 2011;Rankin et al, 2007). This study will examine whether some of these advantages are observed in a new postgraduate course we created: Programming and Systems Development (ProgSD).…”
Section: Team-based Learningmentioning
confidence: 99%
“…In the lab session, although students are supposed to work alone on their practical programming exercises, team members chose to sit together and help each other. Application-focused team programming assignments or team projects were used to foster social interaction where team members would engage in supportive communication practices, including asking for help, sharing information and conflict mediation (Rankin et al, 2007).…”
Section: Implementation Of Modified Tbl For Progsdmentioning
confidence: 99%
“…Wolz et al [19] share their approach to teaching game design across disciplines, including Art, Communications, Computer Science, Interactive Media, Music and Writing. More articles exist that outline pedagogical strategies for incorporating game design for the purpose of enhancing recruitment and retention of computer science majors [5], [12], [13]. Trytten [17] discusses the challenges of teaching introductory Computer Graphics with some game applications in a team-based laboratory setting.…”
Section: Introductionmentioning
confidence: 99%